A Phthalocyanine Derivate Mouthwash to Gargling/Rinsing as an Option to Reduce Clinical Symptoms of COVID-19: Case Series - da Fonseca Orcina B; Vilhena FV; Cardoso de Oliveira R; Marques da Costa Alves L; Araki K; Hiroshi Toma S; Ragghianti Zangrando MS; da Silva Santos PS (Dove Medical Press, 2021)
Bernardo da Fonseca Orcina,1 Fabiano Vieira Vilhena,2 Rodrigo Cardoso de Oliveira,1 Lucas Marques da Costa Alves,3 Koiti Araki,4 Sérgio Hiroshi Toma,4 Mariana Schutzer Ragghianti Zangrando,1 Paulo Sérgio da Silva Santos1 1University of Sao Paulo, Faculty of Dentistry of Bauru, Department of Surgery, Stomatology, Pathology and Radiology, Bauru, SP, Brazil; 2TRIALS – Oral Health & Technologies, Bauru, SP, Brazil; 3Hospital Estadual de Bauru, Bauru, SP, Brazil; 4University of Sao Paulo, Department of Fundamental Chemistry, Institute of Chemistry, Sao Paulo, SP, BrazilCorrespondence: Paulo Sérgio da Silva SantosDepartment of Surgery, Stomatology, Pathology and Radiology, Bauru School of Dentistry, University of Sao Paulo, Al. Dr. Octávio Pinheiro Brisolla, 9 -75, Bauru, CEP 17012-901, São PauloTel +55 14 99670 – 0921Email paulosss@fob.usp.brAim: This case series demonstrated that phthalocyanine derivate mouthwash is a promising alternative for reducing the viral load of SARS-CoV-2 and for clinical improvement of infected patients who presented mild and moderate symptoms.Purpose: The aim of this study was to report a case series of patients diagnosed with COVID-19 that used the phthalocyanine derivate mouthwash to reduce clinical symptoms.Patients and Methods: Eight patients used 5mL of phthalocyanine derivate mouthwash gargling/rinsing for one minute, five times daily, over a fourteen day period. Two measurement scales were applied for each patient in different periods to verify sore throat – VAS – Visual Analogue Scale for Pain and the clinical conditions – PS – Performance Status.Results: All patients presented a significant reduction in clinical symptoms with the use of the mouthwash for gargling/rinsing after few days of use, without hospitalization.Conclusion: The phthalocyanine derivate mouthwash protocol appears as a potential alternative for clinical improvement of COVID-19 infected patients. Daily use of this mouthwash rapidly reduced clinical symptoms such as sore throats, cough and mouth ulcers. Large, high-quality randomized controlled trials with larger sample size are necessary to confirm the effectiveness of this mouthwash protocol against COVID-19.Keywords: mouthwash, sore throats, mouth ulcers, coronavirus infections